Strategies on Brand Managemen in McKings Sizzling Chicken in de Jesus Novaliches Quezon City Towards Developing Brand Recognition: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study, titled "Strategies on Brand Management in Mcking Sizzling Chicken in De JesusNovaliches, Quezon City," was conducted intentionally by the researchers to gather data andinformation that may be used to make this study successful. Mcking's sizzling strategies ontheir price, products, services, brand, and brand awareness are essential. Therefore, theresearchers conducted this study to determine what needs improvement and what Mcking'sneeds to do.The researchers used a tool called Google Forms to collect feedback from 30 customers ofMcking Sizzling Chicken. They asked customers to share their thoughts about the food,services, and brand of the restaurant. Brand strategies: the researchers found that Mckingshad several tactics to attract customers. These included offering budget-friendly meals, givingpriority to both physical stores and online customers, continuously developing new products,and creating engaging social media content. The most effective strategy, according tocustomers, was offering budget meals.The problems encountered by customers are lack of space in the parking lot and dine-in area,gristly meat, wrong orders being served sometimes, difficulty in using cutlery, delay ofservices, and difficulty finding their location. These problems have an impact on their brand.However, to continue growing and recognizing their brand and their business, those problemsneed to be prevented, and solutions need to be made by providing high standards andsatisfying all customers to maintain their loyalty and retention. Mcking's Sizzling Chicken is anaspiring small business that wants to grow as a successful business. Therefore, theresearchers made suggestions and action plans. Conducted market research, Implemented anew pricing strategy, Redesigned store layout, and Trained staff on customer service. Theseaction plans to help Mcking's Sizzling Chicken improve their brand strategies and help themmake more customers recognize their brand and grow as a successful business."
Keywords: Business